2020
DOI: 10.7555/jbr.34.20190037
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate in cancers: from metabolism to signaling

Abstract: Glutamine and glutamate are major bioenergy substrates for normal and cancer cell growth. Cancer cells need more biofuel than normal tissues for energy supply, anti-oxidation activity and biomass production. Genes related to metabolic chains in many cancers are somehow mutated, which makes cancer cells more glutamate dependent. Meanwhile, glutamate is an excitatory neurotransmitter for conducting signals through binding with different types of receptors in central neuron system. Interestingly, increasing evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 104 publications
(148 reference statements)
2
58
1
Order By: Relevance
“…Among them, the transamination reaction from branched-chain amino acids (BCAA) to α-ketoglutarate (α-KG) is catalyzed by either of two types of BCATs, the cytosolic BCAT1 and mitochondrial BCAT2. This reaction produces glutamate, which is synthesized from multiple reactions and participates in important metabolic pathways preferentially utilized by tumor cells to promote survival 6 . The resulting branched-chain keto acids (BCKA) are further catabolized to acetyl- and succinyl-CoA which are intermediates in the TCA cycle 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the transamination reaction from branched-chain amino acids (BCAA) to α-ketoglutarate (α-KG) is catalyzed by either of two types of BCATs, the cytosolic BCAT1 and mitochondrial BCAT2. This reaction produces glutamate, which is synthesized from multiple reactions and participates in important metabolic pathways preferentially utilized by tumor cells to promote survival 6 . The resulting branched-chain keto acids (BCKA) are further catabolized to acetyl- and succinyl-CoA which are intermediates in the TCA cycle 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Gln utilization by the cells involve the conversion of Gln into Glu by glutaminases. Although increased Glu levels were not seen in many of the HGSOC cells, excepting Kuramochi and TYKNU cells ( Figure 6 F), it should be noted that Glu is rapidly metabolized in the cell and utilized as a substrate in multiple pathways involved in energy metabolism and macromolecular synthesis [ 22 ]. One such major pathway involves the conversion of Glu into the neurotransmitter γ-aminobutyrate or γ-aminobutyric acid (GABA) by glutamic acid decarboxylase.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence is emerging that they can elicit diverse non-neuronal response by stimulating their receptors in non-neuronal tissues and recent studies have shown that the extra-neuronal synthesis and release of neurotransmitters cells into the TME by the cancer cells promote tumorigenesis and tumor progression in many cancers [ 23 , 24 ]. Based on previously reported pro-tumorigenic signaling roles of 5-HT [ 23 , 25 , 26 , 27 ], GABA [ 23 , 28 , 29 ], and Glutamate [ 22 , 23 , 30 ] in many other cancer cells, we sought to test their potential role as oncometabolites in HGSOC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Glutamate activates glutamate receptors on cancer cells and results in malignant growth. 38 Immune system research shows that glutamic acid may inhibit cross-reactivity of IgEprimed effector cells reducing the efficacy of forced atopy as cancer immunotherapy. Scientists showed that pre-absorption of serum with glutamic acid resulted in inhibition of IgE reactivity to both inhalable and food allergens, indicating that the carboxyl group of these amino acids is vital in IgE-epitope interactions.…”
Section: Glutamic Acidmentioning
confidence: 99%